Amazonize: uma ferramenta para promover a cultura amazônica - MARQUES, Walder Lobo (2019)
This work describes a tool to support teaching and learning for children focused on the Amazonian culture focused on children from 4 old. The tool was developed to stimulate the senses of the child that in this work were developed the senses of vision, hearing and touch. The development of the tool aimed at the application of good practices of usability and user experience. As it is a teaching tool, stimulating the public in the process of formation, Amazonize presents modules for children who know such as e-books as well as for children who have not yet consolidated their learning process using audiobooks to know the stories. The preschool experience of painting for the recognition of figures, objects and animals is approached in the Amazonize tool with items from the local fauna, providing monochromatic figures for painting, thus allowing the child to develop their local identity. An animal sound recognition module was also developed, along with a challenge to identify the animal related to sound in action, aiming to promote the auditory and memorial perception of those involved.